PENGARUH KINERJA KEUANGAN, KINERJA SOSIAL, DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Yosua; Hanna (Jurnal Akuntansi, 2018)
This study examines the influence of corporate financial performance, corporate social performance, and environmental performance on company value. Company value is measured by Price to Book Value (PBV). Company’s financial performance includes profitability as proxied by Return on Equity Ratio (ROE) and solvency proxied by Debt to Equity Ratio (DER), corporate social performance is proxied by disclosure index which is based on G4 reporting standard published by GRI, and environmental performance is proxied by PROPER index published by the Ministry of Environment. Sample of the companies in this research are all companies listed on the Indonesia Stock Exchange in 2011-2015 consistently and following the PROPER assessment program by the Ministry of Environment and Living. Regression results using SPSS 24 and EViews 6 indicate that the company’s financial performance profitability has a positive effect on corporate value, while the company’s financial performance solvency, corporate social performance, and corporate social performance have no effect on firm value. Keywords: Company Value, Company’s Financial Performance, Corporate Social Performance,Corporate Social Performance.